Pediatric Obesity Etiology, Pathogenesis, and Treatment - Freemark, Michael. (Contemporary Endocrinology, 2010)
Childhood obesity and its co-morbidities -- including type 2 diabetes, hypertension, dyslipidemia, sleep apnea, and fatty liver disease -- have seen striking increases in recent years. Despite a wealth of investigation, there is considerable controversy regarding the etiology of childhood obesity and the optimal approaches for prevention and treatment. Pediatric Obesity: Etiology, Pathogenesis, and Treatment addresses the controversy with a range of features that make it a unique resource for those who care for obese children and their families. Written from a perspective that is international in scope, the distinguished authors re-assess the roles of genetic and environmental factors in the pathogenesis of childhood obesity and critically review new studies of the effects of lifestyle, pharmacologic, and surgical interventions. The evidence-based approach of Pediatric Obesity: Etiology, Pathogenesis, and Treatment provides a comprehensive and invaluable guide for all healthcare providers concerned with the evaluation and care of children with nutritional and metabolic disease and with the societal implications of the obesity epidemic.